Effect of competitive distance on energy expenditure during simulated competition - Foster, G.; de Koning, J. J.; Hettinga, F.; Lampen, J.; Dodge, C.; Bobbert, M.; Porcari, J. P. (International Journal of Sports Medicine, 2004)
Concepts of how athletes should expend their aerobic and anaerobic energetic reserves are generally based on results of tests where an "all out" strategy is imposed on/required from the athlete. We sought to determine how athletes spontaneously expend their energetic reserves when the only instruction was to finish the event in minimal time, as in competition. Well trained, and task habituated, road cyclists (N = 14) completed randomly ordered laboratory time trials of 500 m, 1000 m, 1500 m and 3000 m on a windload braked cycle ergometer. The pattern of aerobic and anaerobic energy use was calculated from total work accomplished and V·O2 during the trials. The events were completed in 40.3 ± 0.6 s, 87.4 ± 4.1 s, 133.8 ± 6.6 s and 296.0± 7.2 s. The peak V·O2 during the terminal 200 m of all events was similar (2.72 ± 0.22, 3.01 ± 0.34, 3.23 ± 0.44 and 3.12 ± 0.13 l × min-1). In all events, the initial power output and anaerobic energy use was high, and decreased to a more or less constant value over the remainder of the event. However, the subjects seemed to reserve some ability to expend energy anaerobically for a terminal acceleration which is contrary to predictions of an "all out" starting strategy. Although the total work accomplished increased with distance (23.14 ± 4.24, 34.14 ± 6.37, 43.54 ± 6.12 and 78.22 ± 8.28 kJ), the energy attributable to anaerobic sources was not significantly different between the rides (17.29 ± 3.82 , 18.68 ± 8.51, 20.60 ± 6.99 and 23.28 ± 9.04 kJ). The results are consistent with the concept that athletes monitor their energetic resources and regulate their energetic output over time in a manner designed to optimize performance.